2011
DOI: 10.1007/s00431-011-1418-5
|View full text |Cite
|
Sign up to set email alerts
|

LEOPARD syndrome (PTPN11, T468M) in three boys fulfilling neurofibromatosis type 1 clinical criteria

Abstract: Noonan syndrome (NS) and neurofibromatosis type 1 (NF1) are well-defined entities. The association of both disorders is called neurofibromatosis-Noonan syndrome (NFNS), a disorder that has been related to mutations in the NF1 gene. Both NS and NFNS display phenotypic overlapping with LEOPARD syndrome (LS), and differential diagnosis between these two entities often represents a challenge for clinicians. We report on three patients (two brothers and a not-related patient) diagnosed as having NFNS. They fulfille… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 33 publications
2
12
0
Order By: Relevance
“…For example, Wu et al [19] reported a de novo NF1 mutation in a woman with a prior diagnosis of LS. Moreover, Carcavilla et al [20] reported three children who filled NF1 clinical criteria but were diagnosed with LS and carried the PTPN11 mutation p.( Thr468Met ), the same mutation detected in our patients. Carcavilla et al [20] suggested that a distinguishing feature for LS might be the diffuse pattern of lentigines, even if they seem to appear later in life than CALMs; this is in accord with our personal observations.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…For example, Wu et al [19] reported a de novo NF1 mutation in a woman with a prior diagnosis of LS. Moreover, Carcavilla et al [20] reported three children who filled NF1 clinical criteria but were diagnosed with LS and carried the PTPN11 mutation p.( Thr468Met ), the same mutation detected in our patients. Carcavilla et al [20] suggested that a distinguishing feature for LS might be the diffuse pattern of lentigines, even if they seem to appear later in life than CALMs; this is in accord with our personal observations.…”
Section: Discussionsupporting
confidence: 79%
“…Moreover, Carcavilla et al [20] reported three children who filled NF1 clinical criteria but were diagnosed with LS and carried the PTPN11 mutation p.( Thr468Met ), the same mutation detected in our patients. Carcavilla et al [20] suggested that a distinguishing feature for LS might be the diffuse pattern of lentigines, even if they seem to appear later in life than CALMs; this is in accord with our personal observations. The patients described in this previous report had cardiomyopathy but lacked other features typical of LS, such as deafness or genital abnormalities.…”
Section: Discussionsupporting
confidence: 79%
“…Noonan syndrome-neurofibromatosis syndrome, which is related to mutations in the NF1 gene 34 congenital heart condition such as hypertrophic cardiomyopathy in patients with Noonan syndrome-neurofibromatosis makes it advisable to start with a genetic study of PTPN11 rather than with NF1. 35 Multiple lentigines and cafe´au lait spots are common in all 3 entities. Just as cafe´au lait spots increase in number and size with age in these entities, multiple lentigines are rare in younger children.…”
Section: Discussionmentioning
confidence: 99%
“…Manifestations may be present from birth, but they usually appear when the child is around 4 or 5 years of age and may even first present in puberty. 2,4,5 Café au lait macules, which are somewhat larger than lentigines, can be seen in 70% to 80% of patients. Lesions that are darker have been called black coffee macules.…”
Section: Discussionmentioning
confidence: 98%